Streptococcus pulmonary empyema after varicella infection in a serologically immunocompetent boy. Issue 4 (August 2014) - Yamaguchi, Hiroshi; Nagumo, Kiyoshi; Sasaki, Daisuke; Aoyagi, Hayato; Kato, Hiroaki; Narita, Yoshiaki; Tamura, Takuya; Kosugiyama, Kiyotaka; Nakashima, Taiji; Kinugawa, Yoshikazu
Abstract Varicella zoster virus (VZV) is the etiologic agent of varicella, and it remains common among children in Japan due to low vaccination rates. It can cause a variety of serious and life‐threatening complications. Generally, the most frequent complication of varicella in healthy children is bacterial superinfection, but empyema after VZV infection is a rare condition. This case report describes a previously healthy 21‐month‐old boy who attended nursery school with a recent varicella and group A β‐hemolytic streptococcus (GABHS) pharyngitis outbreak and who presented with a 7 day history of vesicular rash along with progressive fever. Due to continued mild cough and prolonged fever, however, chest radiography was done, which showed a right pleural effusion. Further computed tomography showed a right pulmonary empyema, and purulent material was drained and eventually grew GABHS. This report hereby describes the development of pleural empyema caused by GABHS after VZV infection in a serologically immunocompetent patient.